The Impact of Body Shaming on Teenage Girls - Novita Maulida Ikmal; Nur Holifah (Pusat Studi Gender Universitas Jember, 2024)
The mass media has an important role in creating a view of ideal body standards. The existence of ideal body standards that emerge in society causes many individuals to experience body shaming. So that society has an indicator of a woman's beauty that is seen from her physical appearance. Body shaming is a person's action or treatment in giving bad comments or criticism about someone's physical appearance, whether related to body condition or appearance, which is done consciously or unconsciously. This form of body shaming is dominated by the color, shape and size of the body in the form of verbal communication and some even takes the form of physical violence. The research method uses a qualitative approach, with descriptive methods. Data was taken from in-depth interviews and journal sources. The results of this research show that body shaming still occurs among teenagers. Often body shaming behavior occurs in middle school or high school. The impacts felt are also very bad, namely stress, depression and loss of self-confidence. As a result, victims of body shaming try to change themselves according to the appearance standards that have been constructed by society. Body shaming behavior can cause discrimination and verbal violence against individuals.